INTROJECTION RAISES THE DEATH DRIVE FOR ACHIEVING PLEASURE PRINCIPLE IN THE HOURS MOVIE (SIGMUND FREUD’S PSYCHOANALISIS APPROACH) - Evi Irawanti Saragih (CrossOver, 2022)
The Hours is a Psychology movie directed by Michael Cunningham and broadcast for the first time in 2002. This movie is about three women whose lives are mutually connected with the story in the novel Mrs. Dalloway by Virginia Woolf. Clarissa Vaughan, a lesbian, decided to take care of Richard, a man and her best friend who suffered from HIV AIDS. Laura Brown, the second character in the movie, has experienced some similarities in her way of life with the character in the novel Mrs. Daloway after she read it. Virginia Woolf, the author of that novel, takes part in the movie as a writer whose work influences other characters. Losing a loved one makes the characters feel unreal happiness. Thus, according to their principle, the characters try to put things from the outside into themselves and raise death drive to achieve pleasure. This study aims to explain how the introjection process carried out by the characters in The Hours movie leads to a death drive and then find out which characters resisted the introjection process and got out of the death drive. The result shows that each character does introjection by imitating and applying what they receive from outside. It raises the death drive, and some of them commit suicide.